Infinitive verbs, verbal agreement and perceived competence / Verbos infinitivos, concordância verbal e competência percebida (Revista de Estudos da Linguagem, 2019)
Abstract: This paper examines how competent speakers of Brazilian Portuguese (BP) sound depending on variable number inflection of infinitive verbs (INF). Recent research has shown high rates of inflected infinitives in syntactic contexts in which it is prescriptively optional, such as adverbial clauses (CANEVER, 2012, 2017). According to that work, inflected infinitives also occur in nonstandard contexts, such as complements of auxiliary verbs, which can be taken as cases of hypercorrection. Informed by these findings and given the prestige usually associated with overtly marking verbal agreement in Brazil (SCHERRE; NARO, 2006, 2014), this study uses a modified matched-guise task (LAMBERT et al., 1960) in order to check whether speakers sound more educated, more intelligent and more formal in their INFflex-guise, and whether these perceptions vary significantly according to the syntactic context, the grammatical person and listeners’ social characteristics (e.g. age). Results show that speakers are judged as more competent-sounding in their uninflected (INFø) guises, contradicting the initial hypothesis. However, further analyses show that this effect is stronger in the hypercorrect context as opposed to the syntactic context in which INFflex is more frequent. These results indicate a relation between frequency of occurrence in production and sociolinguistic perception, with higher rates of use translating into more neutral perceptions. Moreover, older respondents presented stronger reactions to INFflex guises, while younger respondents’ judgments tended to be more neutral. Such age effects suggest a change in progress in the sociolinguistic perceptions associated to (INFflex).Keywords: infinitive verbs; verb-subject agreement; perception.Resumo: Este artigo examina quão competente soa o falante de português brasileiro (PB) a depender da flexão do infinitivo (INF). Pesquisas recentes demonstram altas taxas de infinitivos flexionados em contextos sintáticos opcionais, tais como orações adverbiais (CANEVER, 2012, 2017). De acordo com esses trabalhos, infinitivos flexionados também ocorrem em contextos não padrão, tais como complementos de verbos auxiliares, que podem ser considerados casos de hipercorreção. Considerando-se esses achados e o prestígio usualmente associado à marcação de concordância verbal no Brasil (SCHERRE; NARO, 2006, 2014), este estudo desenvolve uma versão modificada de um teste de estímulos pareados (LAMBERT et al., 1960) para checar se o emprego de INFflex faz com que falantes soem mais educados, mais inteligentes e mais formais, bem como se tais percepções variam a depender do contexto sintático, da pessoa gramatical e de características dos ouvintes (p. ex. idade). Os resultados mostram que falantes foram julgados como mais competentes na presença de INFø, contrariando a hipótese inicial; análises mais detalhadas mostram, porém, que esse efeito é mais forte no contexto de hipercorreção em oposição ao contexto sintático no qual a variante INFflex é mais frequente. Tal resultado indica uma relação entre frequência de ocorrência na produção e percepção sociolinguística, com taxas mais altas de emprego traduzindo-se em percepções mais neutras. Além disso, respondentes mais velhos apresentaram reações mais polarizadas em relação a INFflex enquanto os mais jovens tenderam à neutralidade. Tal efeito de idade sugere uma mudança de percepção sociolinguística em progresso.Palavras-chave: verbos infinivos; concordância verbal; percepção.